Development of Excel-Based Piping Vibration Assessment Model - Mhd Nasser, Asma‘ Khairunnisa‘ (IRC, 2016)
Researches have shown that piping vibration is now happening in all industry which leads to plant downtime, explosion and many other incidents. Despite advances in asset integrity and reliability management in the general area of pressure systems, failures of piping systems in the oil &gas, chemical and petrochemical process industries continues to be a significant problem. Piping systems are subject to vibration induced failures and it cannot be avoided. It is now happening at onshore or offshore production facilities, refineries, and petrochemical plants or even in airplane sector. Basically, it can happen in any industry that has a piping system.